Macro‐scale variation and environmental predictors of flowering and fruiting phenology in the Chinese angiosperm flora. (13th August 2020) - Du, Yanjun; Mao, Lingfeng; Queenborough, Simon A.; Primack, Richard; Comita, Liza S.; Hampe, Arndt; Ma, Keping
Abstract: Aim: The timing of reproduction is a major determinant of the geographical distribution of plant species and resulting patterns of community assembly, yet few studies have assessed how the reproductive phenology of plant assemblages varies across large geographical and environmental gradients. In addition, it remains poorly known to what extent phenological trends and their drivers differ between flowering and fruiting phases or among different growth forms. To address these knowledge gaps, we examined the reproductive phenology and potential climatic drivers in herbaceous and woody species in ecosystems across China that varied in climate (temperate to tropical) seasonality and elevation. Location: China. Methods: We used data from the Flora Republicae Popularis Sinicae to estimate angiosperm flowering ( n = 16, 717 species) and fruiting ( n = 11, 605) phenology for 100 x 100 km grid cells ( n = 943) throughout China. We assessed large‐scale geographical trends in mean flowering and fruiting date and the time needed for fruit development. The relationships of these phenological variables with seven climate variables were examined using both ordinary and spatial linear regression. Results: Higher latitudes and elevations had considerably reduced length of the reproductive season, with later flowering and earlier fruiting than lower latitudes and elevations. Woody plant assemblages flowered markedly earlier and needed three times longer for fruit development, and tended to show steeper geographical trends in reproductive phenology than herbaceous assemblages. Herbs and woody species differed strongly in their climatic triggers of flowering but largely shared the same cues for fruiting. Main conclusions: Woody species compensate for longer seed development times by an earlier onset of flowering, yet reproduction in both life‐forms has stronger climatic constraints. Distinct climatic drivers suggest that herbaceous and woody species assemblages will respond differently to climate change. Overall, our findings underpin the role of reproductive phenology as a key biological mechanism through which climate shapes large‐scale geographical trends in species richness, phylogenetic diversity and community assembly.